Feasibility of 24-Hr Urine Collection for Measurement of Biomarkers in Community-Dwelling Older Adults. (November 2017) - Stuver, Sherri O.; Lyons, Jennifer; Coviello, Andrea; Fredman, Lisa
Biologic markers are becoming a key part of gerontological research, including their measurement at multiple intervals to detect changes over time. This report examined the feasibility and quality of 24-hr urine collection to measure neuroendocrine biomarkers in a community-based sample of older caregivers and non-caregivers. At each interview, participants were instructed on the correct method to collect and store the sample. As incentives, participants selected a day for urine collection within 5 days of the interview, received a reimbursement, and study staff travelled to their home to retrieve the specimen. Between 2008 and 2013, 256 participants were enrolled; all but two participants (99%) provided a baseline urine specimen, of which 93% were considered adequate. Urine collection and quality remained high over three annual follow-up interviews and did not vary by caregiver status or perceived stress level. Our results indicate that 24-hr urine collection is feasible in active, community-dwelling older adults.